The Medieval Latin Talmud and the Tale of the Jew and the Gentile in Albert the Great’s Commentary on the Gospel of Luke - Resnick, Irven (Studies in Christian-Jewish Relations, 2026)
After having completed commentaries upon the works of Pseudo-Dionysius the Areopagite and Aristotle, Albert the Great composed numerous biblical commentaries, including commentaries on many Old Testament texts and all four Gospel texts. In Albert’s commentary on the Gospel of Luke (Super Lucam; ca. 1264-68) he introduces an exemplum from Pseudo-Aristotle's book for Alexander the Great, the De regimine dominorum, The Tale of the Jew and the Gentile. This paper examines Albert’s subtle changes to the text reflecting anti-Jewish images stemming from his role in the condemnation of the Talmud in Paris in 1248.